Long-Term Simultanity Model Of Indonesian Financial Company Value And Debt Policy - Rahmat Hidayat; Rusiadi; Anwar Sanusi; Rahmat Sembiring (International Journal of Science, Technology & Management, 2021)
Competition in financial companies makes each company increasingly improve its performance so that its goals can still be achieved. The main goal of a company is to get profits, to achieve these goals, management is required to make good planning. Likewise, management in a financial company has a goal, where the Debt Policy and Company Value will affect the company's management in achieving profits. This study aims to analyze as much as possible the effectiveness of profitability, dividend payout ratio, asset structure, Free Cash Flow, company size and sales growth and have an influence on the Debt Policy and Company Value. In this study, researchers used the OLS (Ordinary Least Square) method, the Panel Regression method and the Simultaneous / 2SLS method (Two Stage Least Square). Which aims to analyze the influence of independent variables on the dependent variables both separately and jointly and also see the influence of variables in the short and medium term.